Effectiveness of Digital Instructional Modules on Health-Related Physical Fitness Among Secondary School Adolescents in Low and Middle-Income Countries: A Systematic Review - Khoiri, Muhammad Afdhol; Wahyuri, Asep Sujana; Mulia, Fika Dwi (International Journal of Research in Counseling and Education, 2025)
The persistent decline in adolescents’ physical fitness has emerged as a pressing global public-health concern, with low- and middle-income countries (LMICs) facing additional structural constraints in delivering effective school-based physical education. Digital instructional modules have been proposed as flexible, scalable, and personalised alternatives, yet evidence of their impact on objectively measured health-related physical fitness in LMIC contexts remains fragmented. This study aimed to synthesise empirical evidence on the effectiveness of digital instructional modules in improving health-related physical fitness among secondary-school adolescents (aged 15–18 years). A systematic review was conducted following the PRISMA 2020 guidelines using a PICO-based search of Scopus (2021-2026), complemented by ERIC and DOAJ. Of 354 initial records, ten studies met the eligibility criteria and were appraised using the Joanna Briggs Institute (JBI) critical-appraisal tools. Thematic synthesis revealed four intervention typologies: (i) synchronous online classes, (ii) blended learning, (iii) flipped learning, and (iv) mobile-application–based learning, including digitally delivered high-intensity interval training (HIIT). Synchronous, blended, and flipped designs produced the most consistent improvements in cardiorespiratory endurance, muscular strength, and moderate-to-vigorous physical activity (MVPA), whereas mobile-app interventions yielded variable results unless embedded within structured pedagogy. Effects were largely short-term, with sustainability contingent on intrinsic motivation, habit formation, and teacher mediation. Digital technology should therefore be conceptualised as a pedagogical enabler rather than a stand-alone solution. The review contributes a context-sensitive framework for integrating digital modules into physical education in LMICs, particularly Indonesia, and offers policy and pedagogical recommendations for sustainable implementation